Strategic knowledge management in multinational organizations - O'Sullivan 1967- (Information Science Reference, 2008)
"This book presents a comprehensive set of investigations of a wide range of environmental factors, both internal and external, that contribute to the key challenge of complexity in KM. These factors include culture, technology, communications, infrastructure, and learning and leadership structures"--Provided by publisher.